Grow in Concert with Nature : Sustaining East Asia's Water Resources through Green Water Defense - Li, Xiaokai; Turner, Graeme; Jiang, Liping (Washington, DC: World Bank, 2012)
As countries develop, the demand for water increases while water supply becomes less certain and is often not enough to meet demand. In general, pressures from both environment and human activities can increase the likelihood of water scarcity. Such pressures include increased socio-economic development and population growth, change in people's diets, competition for available water among different user sectors and growing climate variability. Climate change is likely to exacerbate the existing demand and supply stresses, particularly when more frequent and extreme droughts and floods, as well as rising sea level are becoming more evident. In temperate, sub-temperate regions, less rainfall and longer dry seasons are expected. In tropical areas, rainfall is predicted to be similar or greater in terms of annual average volumes, more intense and severe storms and seasonal droughts (IPCC, 2007). These pressures will test the effectiveness of water resource management systems in providing a consistent and secure water supply for all users, with minimum externalities. This study will assess advances in management practices, institutional and technological innovations for managing water scarcity sustainably under a changing climate. This study of 'sustaining East Asia's water resources through Green Water Defense (GWD) is a sub-study of the 'towards GWD in East Asia' study and is complemented by another sub-study 'green water defense for flood risk management in East Asia' that focuses on flood management in delta regions.